Transformative online learning post-pandemic: challenges, opportunities, and future trends - Subiyantoro, Singgih (Jurnal Pekommas, 2024)
The Covid-19 pandemic forced a swift and unprecedented transition to online learning in the education sector. This research aims to comprehensively analyze the impact of the pandemic on the educational landscape and investigate how online learning has transformed. This research is grounded in a mixed-methods approach. Quantitative data, including educational institution surveys and student feedback, were collected to gauge the effectiveness of online learning implementation. Qualitative methods such as interviews with educators were employed to gain deeper insights into the experiences and perceptions surrounding the adoption of online learning. The main result of this study indicates that the pandemic has acted as a catalyst for the transformation of education, pushing institutions to embrace online learning technologies and pedagogies on an unprecedented scale. Issues of digital accessibility, pedagogical adaptation, and technological infrastructure also created numerous opportunities to enhance flexibility, inclusivity, and learner-centered approaches. The research concluded that online learning will likely remain integral to education beyond the pandemic. Future trends suggest the convergence of augmented reality, artificial intelligence, and personalized learning, promising to revolutionize the educational landscape further. Academically, this article contributes to the education field by providing valuable insights into the transformative potential of online learning in a post-pandemic context.